Photoaffinity labeling for structural probing within protein - Hatanaka, Yasumaru. ; Hashimoto, Makoto. (Springer, 2020)
This book covers the most up-to-date photoaffinity labeling method to tackle the key loop module involved in the binding process of a bioactive small molecule to its host protein. The book introduces rational points for preparing powerful photoaffinity probes, keys for the efficient analysis of labeled products, and recent successful applications for protein probing. Regarding drug design, the unique topics of the book are the special consideration of the crosslinking potential of recent probes and their application of important receptor proteins . This book presents emerging technologies of photoaffinity labeling to readers who are working in the fields of proteomics, molecular recognition, and drug discovery and development.Preface -- Chapter 1 Multifunctional Photoprobes for Identification of Ligand Sites within Biomolecules -- Chapter 2 Tag-Creation Approaches for Highly Efficient Profiling of Interacting Proteins and Domains -- Chapter 3 Recent Developments in Designing Compact Biological Photoprobes -- Chapter 4 Utilities of Anti-Ligand Antibody and Mass Spectrum to Elucidate Photolabelled Sites -- Chapter 5 Combination of Photoaffinity Label and Site-Directed Antibody for Target Proteins -- Chapter 6 Synthesis of diazirinyl photophore and optically pure diazirinylphenylalanines for photoaffinity labeling -- Chapter 7 Photoreactive biomacromolecules: preparation using photoreactive units and applications for analyzing biological interfaces -- Chapter 8 Covalently capturing protein interactions in living cells by site-specific incorporation of photo-cross-linkable amino acids -- Chapter 9 Use of hexose photolabels to reveal the structure and function of glucose transporters -- Chapter 10 The function of the mammalian peroxisome and analysis of the fatty acid oxidation system by photoaffinity labeling -- Chapter 11 Photoaffinity labeling methods to explore internalization mechanisms of arginine-rich cell-penetrating peptides -- Chapter 12 Photoaffinity Labeling in Drug Discovery Research.